Effectiveness of Dispute Resolution in Religious Courts Through Mediation by Non-Judge Mediators Within Banten - Saiful Majid; Fahadil Amin Al Hasan; Mardi Candra; Arief Isdiman Saleh (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2024)
Mediation is a method of resolving disputes through a negotiation process with the assistance of either a judge or a non-judge mediator. The Supreme Court of Indonesia set a nationwide aim of 25% for settling disputes by mediation in 2023. However, the actual implementation in the jurisdiction of the Banten Religious High Court is only around 20,7% of the defined target, below the national success rate for religious courts, which has reached 39.85%. One of the main factors is the over-reliance on non-judge mediators and the mediator's ability to lead the mediation. Thus, mediation management must be improved, and the capacity of mediators, particularly non-judges, must be increased. This study seeks to discuss the effectiveness of dispute resolution by non-judge mediators and how to maximize the level of success in settling disputes by non-judge mediators. This article is a descriptive qualitative study using normative juridical and empirical approaches. According to the findings of this study, the mediation process in religious court institutions, particularly in the jurisdiction of the Banten Religious High Court, has not been effective because most of the process is directed by non-judge mediators who are less qualified than judge mediators. To increase the success rate of the mediation implementation process, the court must take the following steps: Rewarding non-judge mediators, organizing coaching and training programs for non-judge mediators, determining national mediation settlement targets by involving non-judge mediators, implementing hybrid mediation (between judge mediators and non-judge mediators); and conducting regular evaluations of a non-judge mediator.